Synthesis, Optimization, Characterization and Property of Oxidized Hydroxypropyl Mung Bean Starch. Issue 1 (3rd June 2016) - Hongtao, Tang; Hongbo, Tang; Yanping, Li
Abstract: Mung bean starch (MBS) is very attractive owing to high amylose content. Often the desired functional characteristic cannot be achieved by using a native starch. The synthesis, optimization, characterization and property of oxidized hydroxypropyl mung bean starch (OHMBS) was studied using propylene oxide as an etherified agent, sodium hypochlorite as an oxidant in this article. The best technology conditions for preparing the OHMBS were as follows: reaction temperature 40C, reaction time 2 h, pH 9. The oxidization improved the freeze‐thaw stability of MBS, and increased the blue value of MBS. The hydroxypropylation reduced the blue value of MBS. The hydroxypropylation and oxidization all increased the viscosity stability of the MBS, and changed the thermal stability and melting process of MBS. The introduction of the hydroxypropyl groups into MBS molecules was not in favor of the retrogradation. The retrogradation of OHMBS was in between OMBS and MBS. The onset temperature and peak temperature of OHMBS were intermediate between HMBS and MBS. The end temperature and melting enthalpy of OHMBS were higher than those of HMBS and MBS. The hydroxypropylation could not change basically the crystalline structure of MBS, but the oxidization could destroy the crystalline structure of MBS. Practical Applications: The oxidized hydroxypropyl mung bean starch has the better combination properties compared with the MBS, and are widely used in many industries. For example, OHMBS, as a food additive, is well applied for food products such as a salad cream, a dough conditioner for the bread and a sealing agent in the confectionaries, etc. In paper industry, it can be used as a sizing agent and a coating agent, which will enhance the tension of the paper, improve the strength of the paper surface and printing function. It is also used as an emulsifier, as a replacer of arabic gum and a binding agent in the batter application.